2007
DOI: 10.1091/mbc.e06-06-0530
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated Protein Kinase Kinase 1-dependent Golgi Unlinking Occurs in G2Phase and Promotes the G2/M Cell Cycle Transition

Abstract: Two controversies have emerged regarding the signaling pathways that regulate Golgi disassembly at the G2/M cell cycle transition. The first controversy concerns the role of mitogen-activated protein kinase activator mitogen-activated protein kinase kinase (MEK)1, and the second controversy concerns the participation of Golgi structure in a novel cell cycle “checkpoint.” A potential simultaneous resolution is suggested by the hypothesis that MEK1 triggers Golgi unlinking in late G2 to control G2/M kinetics. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
162
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(183 citation statements)
references
References 60 publications
10
162
0
10
Order By: Relevance
“…The observed phenotype was similar to that previously noted after GM130 or GRASP65 knockdown (Puthenveedu et al, 2006), and quantification using the same image analysis protocol indicated a similar degree of Golgi fragmentation ( Figure 1C). The analysis was then carried out for cells arrested at late G2 phase of the cell cycle when the ribbon undergoes MEKdependent unlinking (Feinstein and Linstedt, 2007). As expected, control cells exhibited an unlinked Golgi, and the appearance of the Golgi in these G2 cells was indistinguishable from cells depleted of GRASP55 and fixed at either S phase or G2 phase (Figure 1, B and C).…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…The observed phenotype was similar to that previously noted after GM130 or GRASP65 knockdown (Puthenveedu et al, 2006), and quantification using the same image analysis protocol indicated a similar degree of Golgi fragmentation ( Figure 1C). The analysis was then carried out for cells arrested at late G2 phase of the cell cycle when the ribbon undergoes MEKdependent unlinking (Feinstein and Linstedt, 2007). As expected, control cells exhibited an unlinked Golgi, and the appearance of the Golgi in these G2 cells was indistinguishable from cells depleted of GRASP55 and fixed at either S phase or G2 phase (Figure 1, B and C).…”
mentioning
confidence: 71%
“…Golgi ribbons become unlinked during late G2 phase Feinstein and Linstedt, 2007) and a block in Golgi disassembly arrests or delays the G2/M transition (Sutterlin et al, 2002;Feinstein and Linstedt, 2007). Premitotic Golgi unlinking depends in part on the constitutive membrane fission activity of CtBP/ BARS (Hidalgo Carcedo et al, 2004; Abbreviations used: CDK, cyclin-dependent protein kinase; GalNAcT2, N-acetylgalactosaminyl transferase-2; GFP, green fluorescent protein; GM130, Golgi matrix protein 130 kDa; GRASP, Golgi reassembly protein; GST, glutathione transferase; MAPK, mitogen-activated protein kinase; RNAi, RNA interference; siRNA, small interfering RNA. …”
mentioning
confidence: 99%
See 3 more Smart Citations